ANALISIS USER EXPERIENCE UNTUK VIRTUAL GALLERY 3D MENGGABUNGKAN PANORAMA FOTO SEBAGAI MEDIA INFORMASI CANDI HINDU BUDHA - Ayung Candra (Universitas Widyatama, 2021)
Virtual reality technology and virtual worlds are one of the technological developments that continue to be developed as a medium for conveying information and content in digital form. The need for innovative media in the era of the Industrial revolution 4.0 is a new necessity and challenge, especially seeing its cultural and historical potential which must be preserved along with the times and technology. One of the topics that is a challenge in media innovation today is the model of information media that was previously designed conventionally in displaying information, especially in the field of history, both pure science and history for learning media. Information on the history of Hindu-Buddhist temples is basically a very interesting history and must be known by everyone, both for children, teenagers, and the general public. This study focuses on designing the user experience (UX) for a 3D virtual gallery combining photo panoramas as a medium of information for Hindu-Buddhist temples in West Java based on ease, efficiency, and usability for users. The method in this research is Design and Development (DnD). The research was conducted using a questionnaire as a research instrument. The research questionnaire distributed consisted of 15 questions grouped into five usability variables. Based on data processing, it was found that of the 5 usability variables used in the questionnaire, only 1 significant variable was used to analyze the usability of the application, namely memorability. Of the 5 variables, the 3D virtual gallery application meets 4 other variables so it can be concluded that the android application does not meet the criteria for Usability, Learnability 85.6%, System Performance 76.9%, Efficiency 79.9%, Memorability 74.2%, Satisfaction 85.04%.